Impacto da reabilitação pulmonar no coping religioso e religiosidade de pacientes com doença pulmonar obstrutiva crônica - Silva, Guilherme Pereira Ferreira da (2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) is frequently accompanied by extrapulmonary manifestations, such as skeletal muscle dysfunction, wasting, osteoporosis, which culminates in the appearance of dyspnoea cough, exercise intolerance, and increased levels of anxiety and depression. These symptoms are associated with difficulties to cope with the disease limits, family dependence, emotional and social restriction and the consequent perspective of death’s proximity, compromising patients' quality of life (QoL), socialization and well-being. Thus, strategies to cope with these challenges are very important. Religious Coping (RC) and Religiosity are considered coping strategies in several chronic diseases, receiving recently increased attention in health research in COPD. Regarding the management of COPD, pulmonary rehabilitation (PR) promotes important benefits including improvements in exercise capacity, depressive symptoms, anxiety, QoL, dyspnea and previous studies showed that PR results in coping styles changes in COPD patients. To the best of our knowledge there is no evidence about de effects of PR in RC and Religiosity in patients with COPD. Objective: to evaluate the impact of PR on RC and Religiosity in patients with COPD; to compare changes in RC and religiosity among patients who presented an important clinical response in the outcomes of functional measures with those who did not present after PR; to investigate associations between changes in RC, Religiosity and exercise capacity, Qol, anxiety, depression, and dyspnoea. Methods: It was performed a non-randomized controlled clinical trial between January 2014 and December 2016. Patients with moderate to very severe COPD and clinically stable were admitted in a PR center at a teaching hospital in Fortaleza-Ceará-Brazil for a PR programme or a control group. 74 patients were enrolled in this study including 38 patients in PR group and 36 patients in control group. PR protocol was composed of a 12-week, 3 sessions per week multidisciplinary programme that involved physical training, nutritional support, psychological counselling and educational sessions. The control group was composed of patients in a waiting list for admission to PR programme and they all were properly medicated and informed about the importance of physical activity practice in their routine. RC, Religiosity, exercise tolerance, Qol, anxiety, depression, and dyspnoea were measured before and after the study protocol. Furthermore, changes in RC and religiosity were compared among patients who presented an important clinical response in functional measures with those who did not present after PR. It is emphasized that the PR and control group did not include an intervention aimed to changing patients’ individual RC styles or religiosity Results: Positive religious coping (PRC) and organizational religious activities (ORA) increases (p=0.01; p<0.001, respectively) while negative religious coping (NRC) decreases (p=0.03) after 12 weeks in PR group (p<0.001). Significant improvements were found in functional measures such as exercise tolerance, QOL, anxiety and depression levels, severity of depressive symptoms and dyspnea after PR. In addition, significantly associations between changes in RC, organizational religiosity with exercise capacity, QoL and depression following PR were observed. No differences were found in control group. Greater PRC, NRC and OR improvements were observed in patients with clinically significant responses in QoL and depression. Conclusions: PR improves RC and OR in patients with COPD and these improvements are related to increases in exercise capacity and QoL and decreases in depression levels. For the subgroup of patients who presented an important clinical response in functional measures, there were greater improvements in positive religious coping, negative religious coping, and organizational religiosity in patients with clinically significant gains in QoL and depression levels.